Analisis Sintaksis Struktur Kalimat Aktif dalam Dongeng 'Asal Mula Tabiat Musang' di Media Tempo - Fadila, Amara Rahma; Mardiansyah, Dandi; Ariz, Muhammad Firhan; Setiawan, Alya Rahmawati; Lisnawati, Iis (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2025)
This research analyzes the structure of active sentences in the fairy tale “Asal Mula Tabiat Musang” published in TEMPO media, focusing on the classification of types of active sentences to understand how syntactic structures contribute to the delivery of narratives. The research method used is descriptive qualitative with literature study technique. The analysis of active sentences includes the identification of ekatransitive (S+P+O), bitransitive (S+P+O+O), and semitransitive (S+P+(O)+(C)+(K)) sentences. The results of the analysis of the 64 sentences in the fairy tales show that the majority are ekatransitive active sentences (24 sentences or 37.5%), followed by sentences that do not belong to the active category (30 sentences or 46.88%), and 10 semitransitive sentences (15.63%). No bitransitive active sentences were found (0%). This finding indicates a tendency to use sentences that focus on actions with a single object, as well as a lack of sentence constructions that involve object-giving or indirect relationships. Variation in sentence structure is maintained by the presence of semitransitive sentences that provide additional descriptive details and context in the narrative.